The relationship of government support, experience and attitude towards business on micro enterprises performance among women entrepreneurs in Batam, Indonesia - Dede Ansyari Guci
The perfonnance of micro enterprise is considered as one of the driving forces for developing countries like Indonesia, where the economy has benefitted greatly from the contribution of micro enterprises. By looking at the importance of micro enterprises in Indonesia, it is important to use the variables that good affect micro enterprises performance. Hence, the aim of this study is to identify whether there are correlations among government support, experience, attitude towards business and the perfonnance of micro enterprises operating in Batam city, Indonesia and to investigate the challenges affecting the perfonnance of micro enterprises in Indonesia. Data examined in this study were collected by using self administered questionnaire. The instrument was adopted from previous researches. A total of 200 respondents of women entrepreneurs have been selected randomly in the field study from three zones in Batam, Indonesia. The data was analyzed by using kolmogrov-smirnov to test the normality. The hypotheseses will be proved by using cronbach's alpha and spearman's correlation. The findings showed the data was not normal, so that the data was analyzed by using non parametric analysis. The results indicate that there are significant and positive correlations among experience, attitude and women entrepreneurs' performance of micro enterprises in Indonesia while there is significant and negative relationship among government support and women entrepreneurs' performance of micro enterprises in Indonesia. It shows that there is a dire need for government support, experience and attitude towards business to be given sufficient concentration as they serve as making better the performance of micro enterprises in Indonesia. This research identifies that the challenges faced by micro enterprises in Indonesia are related to availability of government support, experience and attitude towards business. Thus, it is recommended that the government should undertake policy development work, aimed at making access to fund easier for micro enterprises with growth potential and reduce the interest rate. The government should also support the micro enterprises women entrepreneurs to make use of Entreprenuerial Development Programme (EDP) that is target at improving the knowledge and skill level in the micro enterprises sector. The micro enterprises entrepreneurs should instill the attitude of customer satisfaction, developing their management skill level and man power in order to build a strong capacity for facing these challenges.